The relationship between quality of sports friendships and mental health in Chinese junior high school students: the bidirectional chain mediating effects of sport motivation and exercise adherence - Xing-Yi Li (BMC Public Health)
Abstract Background The purpose of this study was to investigate the effects of quality of sport friendships on mental health and the mediating role of sport motivation and exercise adherence in middle school students. Methods A total of 1,083 middle school students were selected using a combination of cluster sampling and stratified sampling methods. The participants were assessed using the Sport Friendship Quality Scale, Mental Health Scale, Exercise Motivation Scale, and Physical Exercise Adherence Scale. Structural equation modeling was employed to examine the relationships among the four variables. Results (1) The quality of sport friendships positively predicted mental health (β = 0.192, p < 0.01); (2) Sport motivation and exercise adherence act as independent mediators between the quality of sport friendships and mental health respectively; (3) Sport motivation and exercise adherence act as bi-directional chain mediators between the quality of sport friendships and mental health. Conclusion (1) The quality of sports friendships can positively predict mental health, sport motivation, and exercise adherence. (2) The quality of sports friendships not only directly predicts mental health but also indirectly affects mental health through the mediating roles of sport motivation and exercise adherence, as well as the bidirectional chain mediation between the two. This further explains how the quality of sports friendships impacts the mental health of junior high school students, providing significant insights into improving their mental health levels.